(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
In nature fungi widespread because of their ability to grow in different environmental areas, and they transport through the air too long distances away of its essential environment. This study had conducted to investigate the presence of fungi in the indoor air of the transportation (private cars, trucks and buses for children, employees, and students) in Wadi Al shatti and Sebha. The results showed contamination of all transportation included in the study with fungi. Four types of fungi had founded at the two regions. In Wadi Al shatti founded Penicillium sp., Aspergillus niger, Aspergillus Flavus and Aspergillus Parasiticus. In the city of Sebha funded two types are Penicillium sp. and Aspergillus niger. The results also showed the dominance of the genus Penicillium sp. in both regions, employees buses were more contaminate, followed by buses for children, then trucks and private cars in two regions. In general, it had founded the transportation at the Wadi Al shatti region was more contaminate with fungi than the city of Sebha, with a large and diverse fungal presence.